Exposure to azole-resistant Aspergillus fumigatus in Portuguese sawmills - Dias, Marta (2023)
Sawmill workers have an increased risk of adverse respiratory health effects due to wood dust, microorganisms, and metabolite exposure. Knowledge about exposure-response relationships is scarce, with information lacking regarding this transformation sector in Portugal. Among microbial components, fungi and fungal spores and fragments stand as allergens and irritants, due to their high prevalence, under the right circumstances, on wood products (planks, chips) that have been preserved. Aspergillus species can infect the lungs, causing pneumonia-like symptoms that can progress into more severe sickness and are reported as the most common found in sawmills. Moreover, Aspergillus section Fumigati has recently entered the WHO ranking list of most critical fungal pathogens, based on the impact of the fungal disease on public health. While antifungal resistance has been reported in sawmills, there is no data, to date, on occupational exposure to azole-resistant Aspergillus fumigatus (ARAF) in Portuguese sawmills. This study aims to determine the prevalence of azole-resistant Aspergillus fumigatus, followed by the characterization of the distribution of azole-resistance mutations in Aspergillus fumigatus from Portuguese sawmills. The correlation of the exposures with work tasks handled wood products, and seasonal variation will also be made to suggest the most suitable procedures to ensure sawmill workers’ safety.